GROWTH PARAMETERS ESTIMATION OF NILE TILAPIA (Oreochromis niloticus)IN RAWAPENING LAKE, CENTRAL JAVA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
A research was conducted from August 1998 to January 1999. The purpose of this research was to find out growth parameter of Nile tilapia (Oreochromis niloticus) which dominantly inhabit Rawapening lake. The Nile tilapia were caught using small purse seine and lift net. Parameter growth rate was calculated using Forced Gulland and Holt plot, while Loc and to were determined based on empirical formula of Pauly. Total and fishing mortality rates were resolved based on Beverton and Holt formula using growth parameter of the von Bertalanffy Growth equation and the empirical formula. Results of this research showed that the estimated value of the growth coefficient was -1.32 (yearly), the length infinity, L. 34.2 cm, and the theoretical age of fish at length as same as zero, to = -0.11. The von Bertalanffy Growth equation of Nile tilapia (O. niloticus) is Lt = 34.2 (1- e -13"+")). Total mortality was 0.40 per month, natural mortality was 0.17 per month, while fishing mortality was 0.23 per month.